2021
DOI: 10.1371/journal.pone.0256994
|View full text |Cite|
|
Sign up to set email alerts
|

Healthy volunteers in US phase I clinical trials: Sociodemographic characteristics and participation over time

Abstract: Background Increasing the diversity of research participants is an important focus of clinical trials. However, little is known regarding who enrolls as healthy volunteers in Phase I clinical trials, which test the safety and tolerability of investigational new drugs. Despite the risk, healthy volunteers can derive no medical benefit from their participation, and they are financially compensated for enrolling. Objective This study’s purpose is to describe sociodemographic characteristics and clinical trial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…Notably, our sample of intended volunteers is in some ways similar to “typical” healthy volunteer research participants in clinical trials in that they are predominantly male. But they are markedly different from what has been observed in previous studies of phase I study participants [ 24 , 62 ] in that the intended volunteers in our sample were less likely to belong to demographic or socioeconomic groups most vulnerable to exploitation, including ethnic minorities, low-income earners, or unemployed individuals. This suggests that existing concerns about healthy volunteers who participate in other types or research in different contexts, do not necessarily generalize to healthy volunteers who were willing to participate in a COVID-19 HCT early in the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, our sample of intended volunteers is in some ways similar to “typical” healthy volunteer research participants in clinical trials in that they are predominantly male. But they are markedly different from what has been observed in previous studies of phase I study participants [ 24 , 62 ] in that the intended volunteers in our sample were less likely to belong to demographic or socioeconomic groups most vulnerable to exploitation, including ethnic minorities, low-income earners, or unemployed individuals. This suggests that existing concerns about healthy volunteers who participate in other types or research in different contexts, do not necessarily generalize to healthy volunteers who were willing to participate in a COVID-19 HCT early in the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…As for socio-demographic characteristics, our sample presented a higher percentage of individuals employed and with higher education in comparison with healthy volunteers from other countries such as the USA, China, Belgium and Singapore [ 5 , 8 , 25 ]. As lower socio-economic status has been proved to be linked to economic drivers and “serial participation”, high dropout rates, and over-representation of disadvantaged minorities [ 5 7 ] which pose ethical and safety concerns, some authors advocated for implementing and fostering the use of national registers to overcome these issues [ 6 , 28 ] as they guarantee a higher control over participation in clinical trials and a reduction in time and costs related to the recruitment process [ 29 31 ].…”
Section: Discussionmentioning
confidence: 89%
“…When compared to previous data on motivations of healthy volunteers to participate in clinical trials for Ebola and adjuvant influenza vaccines [ 10 ], in our sample, self-reported altruistic motivations played a stronger role while self-interested motivations were extremely less frequent. Although we need to caution about the particular effect that the COVID-19 pandemic may have had on study participants’ motivations, this result fosters discussion about possible differences in motivational profiles between volunteers enrolling in public vs private registers and whether and to what extend these differences play a role in reducing serial participation or early dropout rates which are often reported among US healthy volunteers [ 5 , 24 , 25 ]. Further data are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These “occupational” or “professional” research individuals will seek out and enroll in numerous types of trials throughout a calendar year, at times in quick succession, and may even attempt to participate in more than 1 trial simultaneously 1 . Current literature has indicated that approximately one‐third of those participating in clinical pharmacology studies fall into this “occupational” category 1 . Unfortunately, some participants take an indifferent attitude toward the risks inherent in participating in multiple trials over short periods of time or enrolling in trials sequentially, even though they are well informed and repeatedly warned of the risks by the researchers conducting these trials.…”
mentioning
confidence: 99%